Habitat Characteristics and Distribution of Ternate Island's Endemic Halmahera Shark (Hemiscyllium halmahera) - Firja Hasanah Nabillah; Mohammad Mukhlis Kamal; Sulistiono Sulistiono; Nurhalis Wahidin (Jurnal Ilmu Pertanian Indonesia, 2025)
The Halmahera walking shark (Hemiscyllium halmahera) is a newly discovered endemic species found only in Halmahera's marine waters. Ternate Island's waters are known to provide habitat for the Halmahera walking shark species; the coastal water ecology is primarily made up of seagrass beds and reefs, which help to sustain the species' population. However, knowledge on ecological characteristics and distribution of walking sharks remains scarce. The study aimed to determine the habitat characteristics and distribution of this rare species on Ternate Island's coastal waters. This study was carried out from March to July 2024, with four stations located in the waters of Ternate Island. The data obtained included the number of walking shark sightings, water quality, seagrass bed characteristics, and coral reef conditions. The number of shark appearances varied significantly. The number of appearances was highest at Muhajirin Station and lowest at Kayu Merah Station. Seagrass beds at all four observation stations were categorized as damaged or poor, and coral reefs had begun to erode. Keywords: coral reef, habitat condition, Hemiscyllium halmahera, seagrass bed